PENYULUHAN HUKUM PENCEGAHAN PERKAWINAN USIA DINI PADA SISWA SISWI SMA NEGERI 3 BATAUGA BUTON SELATAN - Amrun Kahar; Hadi Supriyanto (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Legal counseling is an effort to build public awareness from not knowing to knowing. The correlation is very close to empowerment. In order to build awareness of SMA 3 Batauga students about the negative effects of early marriage, this legal counseling is important to do. This counseling delivery method is the delivery of material and interactive discussion. From the results of legal counseling activities on the prevention of early marriage for students of SMA Negeri 3 Batauga Buton Selatan, the benefits that the participants got included: 1. There is legal awareness of the existence of the Marriage Law Number 1 of 1974 as amended by Law Number 16 of 2009. 2. Increasing participants' understanding of the impacts and risks of early marriage.